Decision Making Behaviour of Fisherwomen of Dakshina Kannada District of Karnataka - An Empirical Analysis - Mahesh, V; Swathi Lekshmi, P S; Benakappa, S; Kumar Naik, A S; Kumar, Jitendra; Reddy, S Vijay Kumar (Fishery Technology, 2025)
Among the different sectors of the Indian economy where women contribute significantly, fisheries sector occupies a prime place. Out of the total fisherfolk population of Karnataka, comprising 1 67 429, around 23 000 fisherwomen are actively involved in fisheries related activities such as marketing of fish, net making/repairing, curing/ processing, peeling, labour and other miscellaneous activities. Though, studies have captured the pivotal role played by fisherwomen in income generation for their families, the decision making behavior, a key parameter of their empowerment status, remains an unexplored area. The present study deals with the areas of decision making in which fisherwomen are involved and the influence of socio-economic status on their decision making behavior. The study was undertaken in three selected villages in Dakshina Kannada district of Karnataka using multi stage random sampling method. From the findings, it was observed that, 84.16% of female fresh fish vendors had medium level of decision making behaviour. Fisherwomen were observed to be the sole and independent decision makers with respect to all aspects of fish marketing such as source of fish purchase, rate and quantity to be purchased, transportation, quantity of ice to be used, selling price, time of fish sales, purchasing and hiring of equipment and getting and repaying credits. Results of the multiple regression analysis revealed that, among the profile characteristics studied, the variable namely self-confidence showed a high and positive significant contribution towards decision making behavior of the female fish vendors.